Aesthetics of Employing Digital Sound Effects in Animated Films: سامر طه سالم (Al-Academy, 2020)
When the digital technologies entered the world of cinema production, they boosted the ability of the cinematographic medium to implement various subjects with great accuracy, as the development included all the joints and stages of the cinematic film production whether it is a feature film or an animation. Therefore, the process of film manufacturing by the digital technologies reflects the spirit of the age and the development that humanity has attained. What motivated the researcher to determine the topic of the research, which combines between the sound effects and the animated films under the title (aesthetics of employing digital sound effects in animated films), is the work of the digital technologies. The researcher divided his study into five sections as follows:The methodological framework: included the research problem which is incorporated in the following question: the aesthetics of employing the digital sound effects in the animated films? The importance of the research and the need for it, the research objectives, limits, and identification of terms.The theoretical framework: consists of two sections as follows:The first section: digital sound effects: historical introduction: it included everything concerning the sound effects, i.e. origin, methods of employment, its technological development according the methods adopted in the construction of the sound effect. The second section: the dramatic construction of the animated films: it included the dramatic construction of the animation films. The researcher has come up with a set of indicators which represent the theoretical framework. The research procedures: included the research methodology, research community, research sample and analysis tools in addition to the sample validation.Sample analysis: the researcher analyzed the intentional sample which is an animated film (WALL- E) directed by Andrew Stanton. Results and conclusions: it included the most prominent results the research has come up with: the digital sound effects constituted a clear aesthetic addition in the animated films through expressing the spatial environment in all its minute details as has been shown in the film (WALL- E).The researcher listed the conclusions, recommendations and suggestions and ended the research with a list of references and appendices.